PERANAN CYBERSPACE SEBAGAI PEMBENTUK AKTIVISME POLITIK INTERNET DI INDONESIA - Gofur, Abdul (JUSS (Jurnal Sosial Soedirman), 2018)
The development of science and technology gives the impact in the change of perspective and activities of citizens in communicating. Cyberspace phenomenon or called the virtual world would result in narrowing space, time, and distance so that they are connected to each other. Increasingly internet users in Indonesia need to be utilized as a container in expressing interests, critics and be a public discussion space. As citizens, Internet political activism needs to be positioned as demos for countervailing and supervising the state. In the democracy aspect, the utilization of internet technology becomes a solution for civil society movement. Penetration by social media users in the cyberspace is able to encourage the deliberation of democratic values such as voluntarism, egalitarianism, or networking in contemporary democratic conditions. This paper aims to deepen and add insight about the role of Cyberspace as the form of Internet Political Activism in Indonesia. The method of this research is library research by collecting some related references. Thus, it will improve the knowledge about the role of Cyberspace as the form of internet political activism in Indonesia.